Approximate solutions and parameter estimations of G-protein coupled receptor signal transduction model - Modchang, Charin; Pimpunchat, Busayamas; Lenbury, Yongwimon; Triampo, Wannapong (My University, 2013)
We find approximate analytical solutions of a model for the signal transduction mediated by the G-protein coupled receptor proposed earlier by Modchang et al. The time evolution of the approximate solutions will be explored and compared with numerical solutions of the model. Moreover, an alternative procedure for estimating unknown parameters in the model has been proposed. This alternative parameter estimation method directly uses the exact equilibrium solutions for fitting with the experimental data. We found that this new parameter estimation method can estimate unknown parameter values faster than the method used in previous works. © 2013 Pushpa Publishing House.
Keywords: G-protein coupled receptors; Genetic algorithm; Mathematical model; Signal transduction